2020
DOI: 10.1039/c9se00775j
|View full text |Cite
|
Sign up to set email alerts
|

Boron-doped graphene-supported manganese oxide nanotubes as an efficient non-metal catalyst for the oxygen reduction reaction

Abstract: An efficient, low cost and non-precious hybrid metal catalyst compound consisting of boron-doped graphene nanosheets (BGNSs) and manganese oxide (MnO2) nanotubes is used as a catalyst for the oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…15 The three deconvoluted peaks of rGO centered at 285.9, 286.8, and 288.8 eV are attributed to the C−O hydroxyl group, CO, and O−CO carbonyl bond, respectively. 13 Figure 3c depicts the O 1s spectrum of the Cu-rGO-2 composite. The two deconvoluted peaks centered at 530.4 and 530.9 eV are attributed to Cu 2 O and Cu(OH) 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The three deconvoluted peaks of rGO centered at 285.9, 286.8, and 288.8 eV are attributed to the C−O hydroxyl group, CO, and O−CO carbonyl bond, respectively. 13 Figure 3c depicts the O 1s spectrum of the Cu-rGO-2 composite. The two deconvoluted peaks centered at 530.4 and 530.9 eV are attributed to Cu 2 O and Cu(OH) 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced graphene oxide (rGO), a two-dimensional (2D) nanosheet with sp 2 hybridized networks of carbon atoms, has recently emerged as an attractive material that possesses extraordinary physical and chemical properties, including excellent thermal and electrical conductivities, high chemical stability, rapid charge carrier mobility, and high surface area . Decoration with Cu nanostructures on the surface of rGO nanosheets in the Cu-rGO composite leads to an improvement in the catalytic activity of the composite toward NO 3 – reduction because of the enhancement of the composite’s conductivity and specific surface area after the incorporation of rGO.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the protocols for measuring the surface formation energy and electrostatic potentials were included in our previous reports [16,22,23]. Meanwhile, in the case of RGO, GQDs, and g-C3N4, we used a single layer structure for the aforementioned analysis.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…[15] In particular, carbon-based two-dimensional structures have garnered the most interest as they are capable of delivering excellent electrical conductivity: a highly desirable trait for a fuel cell electrocatalyst. [16,17] Recent investigations have demonstrated that boron/nitrogen/phosphorous/sulphur doped graphene [18][19][20][21] /graphene composites [22,23] /defect graphene [24,25] / graphitic carbon nitride [26] etc. hold great prospects as cathode materials in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%